ANALISIS PENGUASAAN KATA BENDA DALAM BAHASA KHEK PADA MAHASISWA HAKKA PRODI PENDIDIKAN BAHASA MANDARIN - Christiana, Evita; Veronica, Tjen; Afrimonika, Yoanna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Hakka is a dialect of Chinese that is still preserved and used among the Chinese community in Indonesia. The purpose of this article is to learn about the conditions of mastery and difficulties in the use of Hakka nouns by students of the Chinese Language Education Study Program, FKIP Tanjungpura University. This research uses test questions and questionnaires to obtain research results. It is known from the test questions that students' understanding of "animal nouns" reached 76.81%, while reaching 68.26% in "vegetable nouns" and 58.1% in "fruit nouns". This shows that students are more familiar with nouns involving animals, but their understanding of vegetables and fruits still needs to be improved. After analyzing, the author realized that having a basic Khek language helps them in learning Chinese. In addition, the Khek language makes it easier for them to understand Chinese pronunciation and vocabulary. Nonetheless, some students faced difficulties in remember or understand some rarely used vocabulary and errors in articulating certain words.